Strategic compliance of PPA and PPR and level of service rendered in Government agencies. - Hoque, Md. Enamul (BRAC University, 2016)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.